14-3-3z regulates the mitochondrial respiratory reserve linked to platelet phosphatidylserine exposure and procoagulant function - Schoenwaelder, S.; Darbousset, R.; Cranmer, S.; Ramshaw, H.; Orive, S.; Sturgeon, S.; Yuan, Y.; Yao, Y.; Krycer, J.; Woodcock, J.; Maclean, J.; Pitson, S.; et al. (Macmillan Publishers Limited, 2016)
The 14-3-3 family of adaptor proteins regulate diverse cellular functions including cell proliferation, metabolism, adhesion and apoptosis. Platelets express numerous 14-3-3 isoforms, including 14-3- z , which has previously been implicated in regulating GPIb a function. Here we show an important role for 14-3-3 z in regulating arterial thrombosis. Interestingly, this thrombosis defect is not related to alterations in von Willebrand factor (VWF)–GPIb adhesive function or platelet activation, but instead associated with reduced platelet phosphatidylserine (PS) exposure and procoagulant function. Decreased PS exposure in 14-3-3 z -deficient platelets is associated with more sustained levels of metabolic ATP and increased mitochondrial respiratory reserve, independent of alterations in cytosolic calcium flux. Reduced platelet PS exposure in 14-3-3 z -deficient mice does not increase bleeding risk, but results in decreased thrombin generation and protection from pulmonary embolism, leading to prolonged survival. Our studies define an important role for 14-3-3 z in regulating platelet bioenergetics, leading to decreased platelet PS exposure and procoagulant function.